2023
DOI: 10.3390/ijms241813682
|View full text |Cite
|
Sign up to set email alerts
|

APPA Increases Lifespan and Stress Resistance via Lipid Metabolism and Insulin/IGF-1 Signal Pathway in Caenorhabditis elegans

Shiyao Wang,
Dongfa Lin,
Jiaofei Cao
et al.

Abstract: Animal studies have proven that 1-acetyl-5-phenyl-1H-pyrrol-3-yl acetate (APPA) is a powerful antioxidant as a novel aldose reductase inhibitor independently synthesized by our laboratory; however, there is no current information on APPA’s anti-aging mechanism. Therefore, this study examined the impact and mechanism of APPA’s anti-aging and anti-oxidation capacity using the Caenorhabditis elegans model. The results demonstrated that APPA increases C. elegans’ longevity without affecting the typical metabolism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…It has been previously reported that SFN extends lifespan and improves health in C. elegans by regulating IIS pathway signaling and activating the nuclear transcription factor DAF-16/FoxO [47]. Recent studies confirm our assumptions and show that various natural compounds use insulin signaling to enhance the oxidative stress response [97,98]. Notably, in mammals, SFN also regulates Nrf2 activation, the ortholog of the skn-1c gene.…”
Section: Discussionsupporting
confidence: 86%
“…It has been previously reported that SFN extends lifespan and improves health in C. elegans by regulating IIS pathway signaling and activating the nuclear transcription factor DAF-16/FoxO [47]. Recent studies confirm our assumptions and show that various natural compounds use insulin signaling to enhance the oxidative stress response [97,98]. Notably, in mammals, SFN also regulates Nrf2 activation, the ortholog of the skn-1c gene.…”
Section: Discussionsupporting
confidence: 86%
“…DAF-16 (FOXO transcription factor homolog) is a major regulator of the insulin signaling pathway and its overexpression can delay aging and extend lifespan in worms ( Wang et al, 2016 ). skn-1 , gst-4 , and sod-3 are target genes of DAF-16, and all are associated with longevity and protection against oxidative stress ( Liu et al, 2023 ; Wang et al, 2023 ). In this study, we first determined the nuclear localization of DAF-16 and the expression of SKN-1.…”
Section: Resultsmentioning
confidence: 99%